(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of a seeding machine is to put seeds at a desired depth and spacing within the row. Seed spacing uniformity is one of the most important criteria in evaluating planter performance. Therefore, the objective of this research work was to develop an opt-electronic monitoring system for assessment of a mechanical planter seed metering unit performance. The developed system was used to monitor seed flow and to measure seed spacing from the metering system of the row crop planter. The developed system comprised of an optoelectronic sensor for seeds detection, a rotary encoder for forward speed and seed position measurement, amplifiers for adjusting sensors signals, a microcontroller for synchronizing sensors signals, and a PC for operating the program and displaying process. The developed system has been successfully tested on chickpeas seeds at two operating speeds (1.3 m/s and 1.9 m/s). Both numbers and locations of the dropped seeds were assessed. The results indicated that the developed system can be accurately used to detect seeds flow from the metering system with overall system errors of ±4% and ± 10% for speeds of 1.3m/s and 1.9m/s, respectively, compared to manual measurements. Further extensive testing on different crops under actual field conditions are highly recommended to ensure reliability of the developed system.